2007
DOI: 10.1007/s00775-007-0215-0
|View full text |Cite
|
Sign up to set email alerts
|

A new bisphosphonate-containing 99mTc(I) tricarbonyl complex potentially useful as bone-seeking agent: synthesis and biological evaluation

Abstract: Aiming to develop new bone-seeking radiotracers based on the organometallic core fac-[(99m)Tc(CO)(3)](+) with improved radiochemical and biological properties, we have prepared new conjugates with phosphonate pendant groups. The conjugates comprise a chelating unit for metal coordination, which corresponds to a pyrazolyl-containing backbone (pz) with a N,N,N donor-atom set, and a pendant diethyl phosphonate (pz-MPOEt), phosphonic acid (pz-MPOH) or a bisphosphonic acid (pz-BPOH) group for bone targeting. Reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…Thus, we hypothesized that the bone affinity of technetium-99m labeled bisphosphonate would be increased by the design of a bisphosphonate in which the phosphonate groups do not coordinate with technetium-99m. To enable imaging at an earlier time after injection, we and other groups have designed technetium-99m complex-conjugated bisphosphonate compounds based on the concept of bifunctional radiopharmaceuticals [7][8][9][10]. As we expected, some of the novel technetium-99m complex-conjugated Ogawa et al 6/35 bisphosphonate compounds showed superior biodistribution compared with previous compounds.…”
Section: Introductionmentioning
confidence: 86%
“…Thus, we hypothesized that the bone affinity of technetium-99m labeled bisphosphonate would be increased by the design of a bisphosphonate in which the phosphonate groups do not coordinate with technetium-99m. To enable imaging at an earlier time after injection, we and other groups have designed technetium-99m complex-conjugated bisphosphonate compounds based on the concept of bifunctional radiopharmaceuticals [7][8][9][10]. As we expected, some of the novel technetium-99m complex-conjugated Ogawa et al 6/35 bisphosphonate compounds showed superior biodistribution compared with previous compounds.…”
Section: Introductionmentioning
confidence: 86%
“…The synthesis of this complex has already been described but starting from a different synthon [44]. Briefly, pz(CO 2 H) (0.05 mg, 0.131 mmol) reacted with the organometallic precursor [Re(CO) 3 3 ]Br (0.05 mg, 0.13 mmol) in refluxing water for 18 h. After evaporation of the solvent, the resulting residue was purified by preparative RP-HPLC (220 nm, gradient A).…”
Section: Synthesis Of 4-((2-(tert-butoxycarbonylamino)ethyl) (2-(4-(cmentioning
confidence: 98%
“…These conjugates were synthesized as bone-specific estrogens in the hope that they will protect elderly women from bone loss resulting from osteoporosis. A derivative of raloxifene, a selective estrogen receptor or modulator, was obtained using a suitable acid chloride as substrate [137], whereas radioligands, which are selectively bound to bone tissue, have been synthesized by using DCC/HOBt (hydroxybenzotriazol) activation [138] and antibacterial bisphosphonated benzoxazinorifamycin prodrugs using EDCl (1-ethyl-3-(3-dimethylaminopropyl) carbodiimide) [139].…”
Section: Direct Acylation Of Tetraethyl Aminobisphosphonatesmentioning
confidence: 99%